Reflection does not undermine self-interested prosociality - Rand, David G.; Kraft-Todd, Gordon T. (Frontiers in Behavioral Neuroscience, 2014)
The cognitive basis of prosocial behaviour has received considerable recent attention. Previous work using economic games has found that in social dilemmas, intuitive decisions are more prosocial on average. The Social Heuristics Hypothesis (SHH) explains this result by contending that strategies which are successful in daily life become automatized as intuitions. Deliberation then causes participants to adjust to the self-interested strategy in the specific setting at hand. Here we provide further evidence for the SHH by confirming several predictions regarding when and for whom time pressure/delay will and will not alter contributions in a Public Goods Game (PGG). First, we replicate and extend previous results showing that (as predicted by the SHH) trust of daily-life interaction partners and previous experience with economic games moderate the effect of time pressure/delay in social dilemmas. We then confirm a novel prediction of the SHH: that deliberation should not undermine the decision to benefit others when doing so is also individually payoff-maximizing. Our results lend further support to the SHH, and shed light on the role that deliberation plays in social dilemmas.